The limits - Miller, Alice (Auckland University Press, 2014)
The poems in this extraordinary full-length collection by Alice Miller ask you to force yourself beyond your own boundaries. They are curious, restless, bold; they marry lyrical music and intricate metaphor as they search for other human voices beyond the rumblings of the apocalypse and the stubbornness of myth. From bare battlefields to crisp Antarctica to the gates of Troy, from re-written history to love story, they ask for something more from the world than just riding till the spoke breaks. A poet for whom one way's easy but an easy way's / worse, Miller in this collection traces a path.